Perlindungan Data Rekam Medis Pasien dalam Layanan Telemedicine dan Tanggung Jawab Hukum Penyelenggara Platform di Indonesia - Jo Shien Nie; Apriliyanti; Hansed Pither Lasa; Chandra Wahyu Haryo Susilo; Syafrida (Jurnal Hukum Lex Generalis, 2026)
The development of information technology has encouraged the transformation of health services through telemedicine services that allow health services to be carried out remotely by utilizing digital technology. In practice, telemedicine services involve the use of electronic medical records that contain patients' personal data that are confidential and sensitive so that they require adequate legal protection. The problems studied in this study are the form of legal protection for patient medical record data in the implementation of telemedicine services in Indonesia and the legal responsibility of telemedicine platform operators against the leakage or misuse of patient medical record data. This research uses normative legal research methods with a legislative approach and a conceptual approach. The legal materials used consist of primary, secondary and tertiary legal materials that are analyzed qualitatively through analytical descriptive methods. The results of the study show that legal protection of patient medical record data in telemedicine services in Indonesia is regulated in Law Number 17 of 2023 concerning Health, Law Number 27 of 2022 concerning Personal Data Protection, Regulation of the Minister of Health Number 20 of 2019 concerning the Implementation of Telemedicine Services between Health Service Facilities and Regulation of the Minister of Health Number 24 of 2022 concerning Medical Records. Legal protection is carried out preventively through the obligation to maintain the confidentiality and security of patient data and repressively through the provision of sanctions against personal data violations. In addition, telemedicine platform operators have administrative, civil and criminal responsibilities in the event of a leak or misuse of patient medical record data due to negligence in the management of electronic systems.